A Study To Assess The Effect Of Emotional Freedom Technique (EFT) On Stress & Anxiety Among Nurses Working In Covid Ward At Selected Hospital (Journal of Pharmaceutical Negative Results, 2022)
The impact of COVID-19 pandemic on nurses has been significant on their mental & physical health. To minimize their psychological impact Emotional Freedom Technique (EFT) is cost effective, self-administrative successful treatment in very minimum time and highly effective on stress and anxiety. Aim: To assess the effect of Emotional Freedom Technique (EFT) on stress & anxiety among nurses working in covid ward. The focus of the study was analysis of data related to the effect of Emotional Freedom Technique (EFT) on stress & anxiety among nurses in covid ward at Dr. D.Y. Patil Hospital in Pune city.Methodology: An evaluative with One- group pre-test post-test research design was adopted to this study.A Non-probability purposive sampling technique was used for selecting 60 samples of covid ward nurses who met the designated set of criteria in the period of data collection in Dr. D.Y. Patil Hospital. In this study there was one experimental group, 60 covid ward nurses were taught EFT method by the researcher and advised to apply this technique continue for 10days twice a day, early morning & night time before sleep. Telephonic follow up was taken with record.Result: In pre-test, 20% of the nurses working in covid ward had mild stress levels, 75% of them had moderate stress and 5% of them had severe stress. In post-test, 90% of them had mild stress levels and 10% of them had moderate stress and in pre-test, 73.3% of the nurses working in covid ward had mild anxiety levels, 25% of them had moderate anxiety and 1.7% of them had severe anxiety. In post-test, all of them had mild anxiety. The findings related to association of stress and anxiety levels with demographic variables said that p-value corresponding to number of children is small (<= 0.05), the demographic variable number of children and family type was found to have significant association with the stress among nurses working in COVID ward, and the association of stress with demographic variables said that p-values are large (greater than 0.05) So, there is no significant association with the anxiety among the nurses working in covid ward.Conclusion: The research found that in pre-test nurses working in covid ward had mild stress levels and in post-test, all of them had mild anxiety.